Internet-assisted cognitive behavioral therapy with telephone coaching versus an educational control for antenatal depression: protocol for a randomized controlled trial with population-based screening - Sourander, Andre; Korpilahti-Leino, Tarja; Ristkari, Terja; Koffert, Tarja; Arrhenius, Bianca; Ståhlberg, Tiia; Hinkka-Yli-Salomäki, Susanna; Berglund, Mari; Upadhyaya, Subina; Wan Mohd Yunus, Wan Mohd Azam; Sinokki, Atte; Hägg, Riku; et al. (Frontiers in Psychiatry, 2025)
BackgroundUp to 15% of pregnant women suffer from antenatal depression, and there is mounting evidence that the consequences can be devastating for both the woman and her child. Identifying effective treatments is crucial to avoiding the harmful consequences of unrecognized and untreated depression.MethodsThis ongoing research project evaluates the efficacy of the Stronger Together internet-assisted cognitive behavioral therapy (iCBT) with telephone coaching for antenatal depression. It is a large, population-based, two-parallel group, randomized controlled trial. The overarching hypothesis is that iCBT programs are easy to access and affordable and will reduce self-reported symptoms of antenatal depression better than an educational control. The intervention group is also expected to report fewer anxiety symptoms after treatment than the control group. The protocol follows the Standard Protocol Items: Recommendations for Interventional Trials (SPIRIT) guidelines. The study population consists of all Finnish- or Swedish-speaking women, aged ≥18 years, who attend maternity health check-ups at 13–18 weeks of gestation in selected areas of Finland. The aim is to recruit all women who exceed 10 points on the Edinburgh Postnatal Depression Scale and meet other eligibility criteria. Other measures used are the Beck Depression Inventory-II, the Generalized Anxiety Disorder 7-Item Scale, the Pregnancy-Related Anxiety Questionnaire-Revised, the Social Phobia Inventory, and the Perceived Stress Scale. In addition, biological samples (maternal sera and buccal cells) are collected to explore possible moderators for the treatment response. The primary data are collected at baseline and 11 weeks after randomization. The women are randomized 1:1 to the Stronger Together iCBT intervention, which combines seven-weekly themes on a digital platform with weekly telephone coaching, or the educational control group. The CBT components include psychoeducation, behavioral activation, coping with social relationships, cognitive restructuring, and preventing setbacks. The educational control group receives psychoeducational material about wellbeing during pregnancy. Both groups continue to receive standard treatment and maternity health check-ups.DiscussionWe hypothesize that the Stronger Together iCBT intervention will reduce self-rated symptoms of antenatal depression, general and pregnancy-related anxiety, social phobia, and stress. The intervention may offer an accessible and effective treatment for depressed pregnant women.Clinical Trial RegistrationClinicalTrials.gov, identifier ID NCT04223115, Date of first registration: January 10, 2020.